A comparative study of analytical solutions of space-time fractional hyperbolic-like equations with two reliable methods. Issue 1 (2nd January 2019) - Singh, Brajesh Kumar; Gupta, Mukesh
Abstract: This paper deals with a comparative study of analytical solutions of ( n + 1 ) -dimensional space-time fractional hyperbolic-like equations (with Caputo type fractional derivatives) using two reliable semi-analytical methods: "new integral projected differential transform method (NIPDTM)" and "fractional reduced differential transform method (FRDTM)". Three test problems are carried out in order to illustrate the efficiency of these methods. The computed results are also compared with the results fromo various schemes, in the literature. The computed series solutions from either method converge to the exact solutions. FRDTM solutions are easy to compute without using any transformation as compared to NIPDTM, but FRDTM needs more iterations to obtain the solutions with the same accuracy.